Food Pyramid - The Principles of a Balanced Diet - Ioan, SARAC; Monica, BUTNARIU (International Journal of Nutrition, 2020)
The need to understand the relation of man to food, determines the existence of appropriate behavior as well as an attitude in accordance with the modalities that determine human development and evolution, under this structural aspect. A proper diet is the one that provides the amount of nutrients corresponding to personal needs. The food pyramid is the scheme we refer to most in order to know the proportions of foods recommended for consumption. It is a pyramid divided into "layers", each corresponding to a category of foods and the respective quantity.
Keywords: Food pyramid; nutrients; diet; category of foods